BIOCHEMICAL INDICATORS IN THE ORAL FLUID IN CHILDREN WITH CARIES AND GINGIVITIS ON THE BACKGROUND OF EXCESS BODY WEIGHT - Tsushko, I.O.; Dienga, A.E.; Shnaider, S.A.; Horokhivsky, V.N.; Rozhko, P.D.; Rozhko, K.P.; Lysenko, T.O. (World of Medicine and Biology, 2022)
The study is devoted to the research of biochemical indices of oral fluid of 15–18-year-old children with major dental diseases against the background of excess body weight. 88 children aged 15 to 18 participated in clinical examinations, and were divided into 3 groups (the main group – 48 children with main dental diseases and excess body weight, the comparison group – 20 children with main dental diseases and somatically healthy, and the control group – 20 children who were dentally and somatically healthy). Biochemical indices of oral fluid were studied in children. The conducted studies showed that in all children with major dental diseases, a decrease in local non-specific resistance, a weakening of antioxidant protection, an increase in inflammatory processes, a dysbiotic shift, and a violation of functional reactions in the oral cavity were observed.
Keywords: dental indices; biochemical markers; children; excessive body weight; preventive complex